O DESABROCHAR DAS MULHERES DA PRIMAVERA: UMA HISTÓRIA DE PROTAGONISMO E CONTRADIÇÕES – GUARAPUAVA – PR (2003 -2013) - Bochnia , Karina de Fatima Visentin (2017)
The present dissertation is about the protagonism of the Primavera branch Women Movement (MMP - Portuguese abbreviation) representatives in the city of Guarapuava as political agents within their religious practices. The MMP, as turning to a social movement, started using principles defended by Feminist Movements, assuming itself as one of them; at the same time, it had one of its representatives elected in the municipal elections with some political contradictories positions in its basis, what strategically assumed a convergent political proposal in that period. Those facts were possible to analyze through theoretical assumptions defended by Joan Scott and Michel Foucault. The time cut from the present research is between 2003, which is the beginning of the women group activities and 2013, which is the year when the councilor became the deputy-mayor in Guarapuava, holding the position of Women Public Policies Municipal Secretary. In order to fulfill the itinerary of the research, it was used the oral interview methodology, as well as a huge documentation as writing records, books, photographs, the movement blog and folders, national headlines from the Brazilian Bishops National Conference (CNBB – Portuguese abbreviation), Vatican conciliar documents, parish documents, biblical studies formation books, activities reports and the MMP study handbook.